MARKETING COMMUNICATION STRATEGY OF PRODUCTS FOR ELDERLY - Siriamornsith, Ratthavith; Panichpapiboon, Sopark (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The research aimed to 1) investigate factors concerning the marketing communication of products for the elderly, and 2) examine the marketing communication strategy of products for the elderly. The qualitative method employed in this research was an in-depth interview with ten key informants residing in Bangkok. The first group of experts comprised aging wellness experts; the second group consisted of academics, and the third group was communication specialists. The findings revealed that factors concerning the marketing communication of products for the elderly included demographic characteristics, media use behaviors, needs, and health conditions. The media use behaviors of the elderly focused on health-related content, encompassing both contemporary media and traditional media. They utilized these media platforms to enhance their knowledge, pass time, seek entertainment, maintain social relations, and access information that was relevant to their age group. For the marketing communication strategy of products for the elderly, the senders in the communication process must be knowledgeable in what they communicate, following the communication objectives, the elderly’s lifestyle, and needs for receiving information. The senders should also be good communicators. The content must be comprehensible, with clear examples, persuasive storytelling approaches, and attractive content that fosters direct communication, evoking emotion, and trust. The content presentation should feature large font sizes with fewer details, colorful and engaging messages, and illustrations with simple designs. Marketing communication channels targeting the elderly should focus on online platforms, especially Line, Facebook, and YouTube. Despite this, traditional media, like televisions remains a popular choice.